THE ROLE OF THE VOLUNTEER IN NEIGHBORHOOD-BASED PROGRAMS FOR OLDER ADULTS. (11th November 2018) - Glicksman, A; Ring, L; Graham, C
Abstract: Villages and similar programs offer opportunities for older adults to take leadership roles in organizations designed to support aging in place. Other neighborhood level interventions, including NORCs and Age-friendly efforts, also make significant use of volunteers although the programs are usually administered by professionals. Our project, designed to study neighborhood level programs that increase opportunities for socialization and empowerment among older adults and improve access to formal services, collected qualitative data on the role of volunteers in each program (n=8). Both the way in which each program was organized (e.g. a volunteer led Village vs. an agency or government operated senior center), and the primary goal of the program (e.g. focus on building social networks vs. improving service access) helped to shape the role of volunteers in the programs studied. Our presentation will focus on the advantages and challenges in using older adult volunteers to build successful neighborhood level programs.